Author Correction: JAK2V617F mutation drives vascular resident macrophages toward a pathogenic phenotype and promotes dissecting aortic aneurysm (Nature Communications, (2022), 13, 1, (6592), 10.1038/s41467-022-34469-1) - Al-Rifai, Rida; Vandestienne, Marie; Lavillegrand, Jean Rémi; Mirault, Tristan; Cornebise, Julie; Poisson, Johanne; Laurans, Ludivine; Esposito, Bruno; James, Chloé; Mansier, Olivier; Hirsch, Pierre; Favale, Fabrizia; et al. (Nature Communications, 2022)
In this article the affiliation details for Giuseppe Rizzo were incorrectly given as Institute of Experimental Biomedicine, University Hospital Wuerzburg, Germany and Helmholtz Institute for RNA-based Infection Research (HIRI), Helmholtz-Center for Infection Research (HZI); Würzburg, Germany but should have been Institute of Experimental Biomedicine, University Hospital Wuerzburg, Würzburg, Germany. Alma Zernecke was incorrectly given as Helmholtz Institute for RNA-based Infection Research (HIRI), Helmholtz-Center for Infection Research (HZI); Würzburg, Germany but should have been Institute of Experimental Biomedicine, University Hospital Wuerzburg, Würzburg, Germany. Clément Cochain was incorrectly given as Institute of Experimental Biomedicine, University Hospital Wuerzburg, Germany and Helmholtz Institute for RNA-based Infection Research (HIRI), Helmholtz-Center for Infection Research (HZI); Würzburg, Germany but should have been Institute of Experimental Biomedicine, University Hospital Wuerzburg, Würzburg, Germany. The original article has been corrected.
CRIS-Team Scopus Importer:2023-03-23